(untitled) (INNOVATIVE ECONOMY, 2023)
Yasyshena V.V. MODEL FOR IMPROVING THE METHODOLOGY AND ORGANIZATION OF THE ACCOUNTING OF INTANGIBLE ASSETS AND GOODWILL Purpose. The aim of the article is the development of a model for improving the methodology and organization of accounting for intangible assets and goodwill in the accounting (financial) accounting system. Methodology of research. The theoretical basis of the research is the scientific works of domestic and foreign scientists on the problems of research in the areas of improving accounting, the formation of reporting indicators and the management of intangible assets and goodwill. The methodological basis of the research is general scientific methods (synthesis, analysis, abstraction, comparison, generalization, grouping, systematization) – when forming proposals for improving the used elements of the accounting method, for the formation of new knowledge about the intangible resources of the enterprise, Illustrative method is used for a schematic representation of the model of improvement of the methodology and organization of accounting of intangible assets and goodwill, abstract and logical method – for formulating research conclusions. Findings. A model for improving the methodological and organizational foundations of the concept of accounting (financial) accounting for intangible assets and goodwill is presented, covering the following areas: expanding the principles of accounting (financial) accounting; clarification of the concept of "intangible assets"; highlighting the main aspects of recognition of intangible assets; expansion of the intangible assets classification; improvement of the organizational foundations of the accounting policy through the separation of its constituent and structural elements in terms of accounting (financial) accounting; development of Methodological recommendations for the application of typical forms of primary accounting of intangible assets and goodwill; improvement of the approaches to the inventory of NMAs by dividing them into those for which a documentary check is sufficient and those that additionally require a check on the quality of functioning; unification of intangible assets objects and systematization of approaches and methods of their assessment according to international and domestic standards of assessment and accounting; improvement of synthetic and analytical accounting of intangible assets and goodwill; improvement of form No. 1 "Balance (Financial Statement), Management Report, form No. 5 "Notes to the annual financial statements" in the part of disclosure of information about intangible assets and goodwill; improvement of the amortization policy in terms of taking into account the features of various types of intangible assets for choosing a method of amortization using slow-down methods and developing an algorithm for establishing the feasibility of its accrual to some types of intangible assets; improvement of the content of the regulatory and legal framework regarding accounting operations of intangible assets and goodwill. Ways to improve the methodology and organization of accounting and the formation of financial reporting indicators in the part of intangible assets and goodwill are substantiated and proposed. Originality. The conceptual foundations of the model for improving the methodology and organization of accounting for intangible assets and goodwill in the accounting (financial) accounting system have been established and substantiated. This, unlike the existing approach, will systematically cover all the main and problematic aspects, the consideration of which will affect the objective reflection of intangible assets and goodwill in the accounting and financial statements of the enterprise for their effective use. Practical value. Implementation of the recommendations proposed in the publication on improving the methodology and organization of accounting for intangible assets and goodwill in the accounting (financial) accounting system will contribute to increasing the efficiency of their use and management. The results of the research found practical application at enterprises of Ukraine. Key words: intangible assets, goodwill, accounting, accounting policy, classification, documentation, valuation, inventory, depreciation, financial reporting.